2022
DOI: 10.3390/sym14030436
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the E⊗e Jahn–Teller Potential Energy Surfaces by Differential Geometry Tools

Abstract: The term ‘mathematical chemistry’ is mostly associated with applications of graph theory in topological issues of 3D chemical structures, thought of as a collection of atoms as dots and bonds as lines. We propose here new directions in this field, coming from the side of theoretical chemistry approached with modern computational tools. Possible challenges are proposed in using ancillary tools of differential geometry for examining the potential energy surfaces of certain specific structural prototypes. Concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To our knowledge, similar models of semi-symmetric non-metric connections are not given. Then, we expect to develop models and applications of semi-symmetric non-metric connections in some other fields, e.g., in quantum and theoretical chemistry, directions in which the first author of this paper and her co-workers took preliminary steps, using the tools of differential geometry (see [4], [12]).…”
Section: Applications In Other Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, similar models of semi-symmetric non-metric connections are not given. Then, we expect to develop models and applications of semi-symmetric non-metric connections in some other fields, e.g., in quantum and theoretical chemistry, directions in which the first author of this paper and her co-workers took preliminary steps, using the tools of differential geometry (see [4], [12]).…”
Section: Applications In Other Fieldsmentioning
confidence: 99%
“…For instance, one may devise applications in the topology of multidimensional surfaces representing the energy dependence of chemical edifices as function of symmetry-classified changes in molecular geometries, with relevance in modeling physical properties and chemical transformations of molecules and materials. In this sense, a special situation, which deserves further attention, with the help of analytic tools outlined here, would be the case of spontaneous breaking of molecular symmetry in systems with energy surfaces containing the so-called conical intersections (see [4]). We foresee that the use conformal changes and semi-symmetric connections could open a new geometric perspective on such problems, pertaining to molecular symmetry and chemical dynamics.…”
Section: Applications In Other Fieldsmentioning
confidence: 99%
“…is a subproblem when predicting the structure of matter, particularly the structure of a crystal, regarding information that makes it possible to predict almost all of its properties, and the design of mathematical models for the closest symmetrical packing is an important and a challenging task in the practical application of optimization theory in theoretical chemistry). In [2], a characterization of the E⊗e Jahn-Teller (a spontaneous symmetry-breaking phenomenon, also known as a case of conical intersection) potential energy surfaces by differential geometry tools was presented. In [3], a synthesis of 2-pyridyltellurenyl bromide via Br 2 oxidative cleavage of the Te-Te bond of dipyridylditelluride was reported, and a single-crystal X-ray diffraction analysis of 2-pyridyltellurenyl bromide demonstrated that the Te atom of 2-pyridyltellurenyl bromide was involved in four different noncovalent contacts (Te• • • Te, Te• • • Br, and Te• • • N), forming a 3D supramolecular symmetrical framework.…”
mentioning
confidence: 99%